Diagnostic accuracy and adequacy of computed tomography versus fluoroscopy-guided percutaneous transpendicular biopsy of spinal lesions - Zakaria@Mohamad, Zamzuri; A Rahim, Abdullah; Ren, Yi Kow; Karupiah, Rajandra Kumar; Zainal Abidin, Nur Azlin; Mohamad, Fazir (Cureus, Inc, 2022)
Background Transpedicular biopsy of spinal lesions is imperative for the generation of a definite diagnosis. Thus far, literature comparing the accuracy and adequacy between fluoroscopy-guided and computed tomography (CT)-guided transpedicular biopsy of spinal lesions is scarce. We aim to compare the accuracy and adequacy of samples collected with the two techniques at the largest tertiary hospital in Malaysia.